Instruments to assess function or functionality in adults after a burn injury: A systematic review. Issue 5 (August 2021) - Itakussu, Edna Yukimi; Morita, Andrea Akemi; Kakitsuka, Emely Emi; Pitta, Fabio; Cavalheri, Vinicius; Hernandes, Nidia Aparecida
Highlights: A vast quantity of tools is available for assessment of functionality of burns. Most tools were not specifically developed for burns nor are validated for them. Few studies tested the measurement properties of the tools. Most of the identified tools have good clinical utility. Abstract: Introduction: Assessment of functionality or function, through valid and reliable instruments, is essential during rehabilitation of adults after a burn injury. Currently, there is no consensus in the literature regarding the most appropriate tool that should be used to assess function or functionality; there is also no synthesis of the current studies published in this area. Objectives: To investigate and report the instruments used to assess function or functionality in adults after a burn injury; to identify the characteristics and evidence on their measurement properties; and to evaluate their clinical utility. Methods: We systematically searched the literature via six electronic databases and via screening reference lists of relevant studies. The review was registered in PROSPERO (CRD42016048065) and reported according to the PRISMA statement. Studies in which function or functionality of upper and/or lower limbs of adults after a burn injury was assessed were included. Exclusion criteria comprised studies in pediatric populations and conference abstracts. Results: Thirty-four studies were included. Twelve questionnaires and seven objective tests for function or functionality were identified. Three specific tools were found; four generic instruments have been validated in burns. Nine studies evaluated the instruments' measurement properties, presenting at least one property classified as 'fair' quality. Finally, 18 instruments demonstrated clinical utility. Conclusion: This systematic review demonstrated that most instruments used to assess function or functionality in adults with a burn injury have not been specifically developed for this population and had their measurement properties poorly studied. Conversely, almost all instruments had clinical utility.